Porous carbon material with half-slope platform type aperture structure, preparation method and application
By performing Mannich reaction and crosslinking on alkali lignin, a porous carbon material with a half-slope platform-type pore size structure is formed, and silicon is deposited through chemical vapor deposition technology, the problem of pyrolysis instability of lignin carbonization is solved, and the problem of pyrolysis instability of lignin carbonization is achieved Effective suppression of silicon volume expansion and improved stability of electrode structure improve the cycle stability and conductivity of lithium-ion batteries.
Patent Information
- Application Number
- CN202411338802.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
When lignin is pyrolyzed, local areas are prone to lose stability, resulting in uneven shrinkage of the porous carbon material structure, which cannot effectively inhibit the expansion of silicon volume, resulting in poor circulation performance of dispersed silicon-carbon composites.
Polyamines were grafted on alkali lignin through Mannich reaction, and the alkali lignin was crosslinked using aliphatic dialdehyde and dialdehyde thiophene derivatives as crosslinking agents to form a half-slope platform-type pore size structure The porous carbon material is combined with chemical vapor deposition technology to deposit silicon to produce a dispersed silicon-carbon composite material.
The formed porous carbon material has the ability to strongly suppress silicon volume expansion, maintain the stability of the electrode structure and circulation capacity, improve the cycle stability and conductivity of lithium-ion batteries, and extend the service life of the battery.
Smart Images

Figure CN119218991A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous carbon materials, and in particular relates to a porous carbon material with a half-slope platform-type pore size structure, a preparation method and an application thereof. Background Art
[0002] With the rapid development of lithium-ion batteries, the development of high-energy-density lithium-ion battery negative electrode materials has become an urgent need in the current lithium-ion battery field. Because single-element silicon has the highest theoretical lithium storage capacity (about 4200mAh / g) and a lower lithium desorption voltage platform (0.4-0.5V), it is considered to be one of the most promising negative electrode materials to replace graphite. However, silicon negative electrodes have been slow to be used commercially. This is because silicon will produce a huge volume effect during the lithium deintercalation process. Silicon particles will break or even pulverize due to huge stress, which will cause the active material on the silicon electrode to pulverize and peel off, resulting in loss of electrical contact between particles and between particles and current collectors, which will lead to a sharp decline in battery capacity or even complete failure.
[0003] To solve this problem, researchers have done a lot of research on suppressing / reducing the volume effect of silicon and improving its conductivity. Dispersed silicon-carbon composite materials are one of the current research hotspots. Dispersed silicon-carbon composite materials, also known as molecular contact type, refer to the contact of silicon-carbon materials in the composite material in molecular form. Silicon is highly dispersed in the carbon layer. The carbon material, as a dispersed matrix, can not only limit the volume change of silicon, but also serve as a conductive network to maintain good electrical contact between electrodes during the charge and discharge process, such as the porous carbon-silicon composite material and its preparation method disclosed in patent CN103840140B, and a silicon-carbon composite material and its preparation method and application, and lithium-ion secondary battery disclosed in patent CN116742002A.
[0004] The porous carbon-silicon composite materials prepared above mostly use sucrose, glucose, polyvinyl chloride, asphalt, polyacrylonitrile, starch, etc. as precursors, which are pyrolyzed to obtain dispersed matrix porous carbon materials, and then vapor deposited to obtain a relatively ideal dispersed system. This composite form can inhibit the volume expansion of silicon, thereby maintaining good structural stability and cycle capacity of the electrode.
[0005] However, in recent years, with the continuous development of industrial society, the large-scale development and utilization of non-renewable petrochemical resources has caused resource crises, environmental pollution and energy problems that have seriously restricted the sustainable development of human society. The efficient development of natural renewable green biomass resources and their application in new energy materials with excellent performance, low cost, green and high efficiency is one of the main trends in current research and development. Lignin is a very abundant natural renewable biomass resource. Its content in plants is second only to cellulose. Its molecular structure has a three-dimensional network characteristic, rich in a large number of aromatic groups and oxygen-containing functional groups, and its carbon content is more than 60%. At present, the comprehensive utilization rate of industrial lignin from the pulp and paper and biorefining industries is only about 10%, and most of it is discharged as waste or burned as low-value fuel. If its carbonization pyrolysis is used as a dispersed matrix-porous carbon material for dispersed silicon-carbon composite materials, it can not only achieve effective utilization of resources, but also alleviate environmental pollution problems. Although lignin has three-dimensional network characteristics, it is not a highly cross-linked structure. During carbonization and pyrolysis, it is easy for local areas to lose stability, and the overall structure shrinks unevenly, leading to the formation of cracks, holes and even collapse. If this porous carbon material is used as a dispersed matrix for dispersed silicon-carbon composite materials, it has low strength, cannot effectively inhibit the volume expansion of silicon, and has poor cycle performance.
[0006] Therefore, it is necessary to modify lignin to prepare dispersed silicon-carbon composite materials that can inhibit the volume expansion of silicon and maintain good structural stability and cycle capacity of the electrode. Summary of the invention
[0007] To solve the above problems, the present invention provides a porous carbon material with a half-slope platform-type pore structure, a preparation method and an application thereof. The present invention first uses alkali lignin, polyamine and formaldehyde solution as raw materials to obtain amino alkali lignin by Mannich reaction, then cross-links it with a dialdehyde derivative as a cross-linking agent, and finally mixes it with a porogen to carbonize and activate it to obtain a porous carbon material with a half-slope platform-type pore structure. The dispersed silicon-carbon composite material obtained by depositing silicon on the porous carbon material through chemical vapor deposition technology has a strong ability to inhibit the volume expansion of silicon and can maintain good structural stability and cycle capacity of the electrode.
[0008] In order to achieve the above purpose, the following technical solutions are adopted:
[0009] A method for preparing a porous carbon material with a half-slope platform-type pore structure comprises the following steps:
[0010] 2) adding alkali lignin and polyamine to water, adjusting the pH, stirring until completely dissolved, adding formaldehyde solution under stirring conditions for hydrothermal reaction, adding isopropanol after the reaction until no precipitation is produced, filtering, washing, and drying to obtain amination alkali lignin;
[0011] 2) dissolving the amination alkali lignin in an organic solvent, adding a dialdehyde mixture, heating to reflux state to carry out a cross-linking reaction, filtering after the reaction, washing, drying, and grinding to obtain a precursor;
[0012] 3) The precursor and the porogen are mixed evenly, and then carbonized under an inert atmosphere. The carbonized material is then mixed with an alkali solution and activated in an inert atmosphere, and then cooled, acid-washed, washed with water, and dried to obtain a porous carbon material with a semi-slope platform-type pore structure;
[0013] Step 1) The polyamine is selected from one or a combination of two or more of diethylenetriamine, triethylenetetramine and tetraethylenepentamine, preferably tetraethylenepentamine.
[0014] Step 2) The dialdehyde derivative is a mixture of an aliphatic dialdehyde and a dialdehyde-based thiophene derivative in a mass ratio of 5:7-10.
[0015] The porous carbon material prepared by the above method is a hierarchical porous structure with coexisting micro / mesopores, and its mesoporous area is small and has a broad peak distribution, that is, there is a half-slope platform-type mesoporous transition zone between the micropores and the macropores. This pore structure has good connectivity, and the silicon source gas can smoothly diffuse into the micropores deep inside the material, making full use of all the adsorption sites, improving the dispersion uniformity of silicon particles in the porous carbon material, effectively reducing the generation of local defects, maintaining the stability of the electrode structure, and improving the cycle stability of the battery.
[0016] Step 1) The preparation method of the alkali lignin is not particularly limited, and it can be prepared by acid precipitation of bamboo pulp or straw pulp alkali papermaking black liquor, specifically: adjust the pH of bamboo pulp or straw pulp alkali papermaking black liquor to 7-9 with inorganic acid, filter and take the filtrate; then continue to adjust the pH to 2-3 with inorganic acid, stir at 70℃-100℃ for 6h-9h, filter, wash 2-3 times and dry to obtain alkali lignin. The mass volume ratio of the alkali lignin and water is 1g:20-40mL. The mass ratio of the alkali lignin, polyamine and formaldehyde solution is 15-20:4-6:5-8. The pH is adjusted to 10-11 with an alkali solution with a concentration of 0.5-1mol / L, and the alkali solution is selected from one or a combination of two or more of NaOH and KOH solutions. The concentration of the formaldehyde solution is 30-40wt%. The hydrothermal reaction temperature is 40-80℃, and the reaction time is 1-3h. The washing is washing with water until neutrality occurs. The drying is drying at 60-80° C. until constant weight occurs.
[0017] The mass ratio of the dialdehyde mixture in step 2) to the polyamine in step 1) is 0.5-0.8:1. The aliphatic dialdehyde is a C8-C12 aliphatic dialdehyde, selected from one or a combination of two or more of heptanedialdehyde, octanedial, nonanedialdehyde, and dodecanedial, preferably dodecanedial. The aldehyde thiophene derivative is selected from one or a combination of two or more of 3,4-thiophene dicarboxaldehyde, 2,3-thiophene dicarboxaldehyde, 2,2'-bithiophene-5,5'-dicarboxaldehyde, 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde, preferably 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde. The reaction time is 4-6h. The organic solvent is selected from one or a combination of two or more of chloroform, pyridine, dichloromethane, ethanol, acetone, dioxane, and ethyl acetate, preferably a mixed solvent of dioxane and dichloromethane in a volume ratio of 7:2-4, preferably 7:3. The grinding is grinding to an average particle size of 40-80 meshes.
[0018] Step 3) The mass ratio of the precursor to the porogen is 1:1-2. The porogen is selected from one or a combination of two or more of ammonium carbonate, urea, ammonium bicarbonate, ammonium formate, ammonium acetate, and ammonium oxalate. The carbonization is heated to 400-500°C at a heating rate of 5-10°C / min and kept at a constant temperature for 1-3h; the alkali solution is one or a combination of two or more of NaOH and KOH solutions with a concentration of 10-30wt%. The mass volume ratio of the carbonized material to the alkali solution is 1g:1-4mL. The activation is heated to 500-800°C at a rate of 1-20°C / min and kept at a constant temperature for 0.5-3h. The cooling is cooling to room temperature. The pickling is washing 1-3 times with a hydrochloric acid solution with a concentration of 0.5-1.5mol / L, and the water washing is washing to neutrality. The drying is drying at 60-100°C to constant weight.
[0019] A porous carbon material with a half-slope platform pore structure is prepared by the method for preparing a porous carbon material with a half-slope platform pore structure.
[0020] A method for preparing a dispersed silicon-carbon composite material comprises the steps of evacuating a chemical vapor deposition device, placing the porous carbon material with a half-slope platform-type pore structure in a chemical vapor deposition chamber, introducing a silicon source gas to perform vapor deposition of silicon, and obtaining the dispersed silicon-carbon composite material.
[0021] The temperature in the chemical vapor deposition chamber is 500-600°C. The time for introducing the mixed gas is 1-4h, the flow rate of the mixed gas is 120-180mL / min, the pressure in the chemical vapor deposition chamber is 0.1-0.3MPa, and the silicon source gas and the inert gas are mixed in a volume ratio of 5-10:90-95. The silicon source gas is selected from one or a combination of two or more of monosilane and disilane. The inert gas is not particularly limited, including but not limited to one or a combination of two of argon and nitrogen.
[0022] A lithium-ion battery comprises a negative electrode, wherein the negative electrode comprises the above-mentioned dispersed silicon-carbon composite material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention firstly grafts a polyamine onto the surface of alkali lignin through the Mannich reaction, then uses a dialdehyde mixture of an aliphatic dialdehyde and a dialdehyde-based thiophene derivative as a crosslinking agent, and crosslinks and solidifies the alkali lignin through the reaction between the aldehyde group and the amino group to form a complex highly crosslinked structure, so as to reduce the generation of defects during the carbonization and pyrolysis of the alkali lignin and improve the ability to inhibit the volume expansion of silicon.
[0025] In addition, by adjusting the relative amount of dialdehyde derivatives, controlling the amount of residual amino groups on the polyamine, and combining with porogens, the porous carbon material evolves from a single structure dominated by micropores to a hierarchical porous structure with coexistence of micro / mesopores, and the porous carbon material is endowed with small and broad-peak distributed mesopores, that is, there is a half-slope platform-type mesoporous transition zone between the micropores and the macropores. This pore structure has good connectivity, and the silicon source gas can diffuse smoothly into the micropores deep inside the material, making full use of all the adsorption sites, improving the dispersion uniformity of silicon particles in the porous carbon material, effectively reducing the generation of local defects, maintaining the stability of the electrode structure, and improving the cycle stability of the battery.
[0026] The present invention introduces sulfur and nitrogen elements into the porous carbon material through the grafting of polyamines and the cross-linking reaction of dialdehyde derivatives, which is beneficial to improving the conductivity of the dispersed silicon-carbon composite material, reducing the attenuation rate of the material, and extending the cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the pore size distribution diagram of the porous carbon material prepared in step 4) of Example 1;
[0028] Figure 2 This is the pore size distribution diagram of the porous carbon material prepared in step 4) of comparative example 3. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0030] Alkaline straw pulp papermaking black liquor was purchased from Beijing Paper Mill No. 7 Co., Ltd.
[0031] Example 1
[0032] 1) The pH of the straw pulp alkaline papermaking black liquor is adjusted to 7 with a hydrochloric acid solution with a concentration of 1 mol / L, and the filtrate is filtered and taken; then the pH is adjusted to 2 with a hydrochloric acid solution with a concentration of 1 mol / L, stirred at 100°C for 6 hours, filtered, washed with water for 3 times, and dried at 60°C to constant weight to obtain alkaline lignin.
[0033] 2) 2000 g of alkali lignin and 600 g of tetraethylenepentamine were added to 8000 mL of water, the pH was adjusted to 11 with a 1 mol / L sodium hydroxide solution, and the mixture was stirred until completely dissolved. Under stirring conditions, 800 g of a 37 wt % formaldehyde solution was added to carry out a hydrothermal reaction at 80° C. for 1.5 h. After the reaction, isopropanol was added until no precipitation was produced, the mixture was filtered, washed with water until neutral, and dried at 80° C. until constant weight to obtain aminated alkali lignin;
[0034] 3) The amination alkali lignin obtained in step 2) was dissolved in 8000 mL of a mixed solvent of dioxane and dichloromethane in a volume ratio of 7:3, and 300 g of a dialdehyde mixture of dodecanedial and 2,2':5',2"-terthiophene-5,5"-diformaldehyde in a mass ratio of 5:10 was added, and the cross-linking reaction was carried out under reflux for 4 hours. After the reaction was completed, the mixture was filtered, washed with water 3 times, dried, and ground into 80 mesh to obtain a precursor;
[0035] 4) Take 1000g of the precursor prepared according to method 3) and mix it evenly with 1000g of urea, then heat it to 500℃ at a rate of 10℃ / min under a nitrogen atmosphere, and keep it at a constant temperature for 1h for carbonization. The carbonized material after carbonization is mixed evenly with a 30wt% sodium hydroxide solution at a mass volume ratio of 1g:4mL, and activate it in a nitrogen atmosphere. The activation procedure is to heat it to 800℃ at a rate of 10℃ / min and keep it at a constant temperature for 3h, cool it naturally to room temperature, wash it with a hydrochloric acid solution with a concentration of 1mol / L 3 times, wash it with water to neutrality, and dry it at 60℃ to constant weight to obtain a porous carbon material with a semi-slope platform pore structure.
[0036] 5) After the chemical vapor deposition equipment is evacuated, the porous carbon material with a half-slope platform-type pore structure is placed in a chemical vapor deposition chamber, and a mixed gas consisting of argon and monosilane in a mass ratio of 5:95 is introduced at a flow rate of 180 mL / min for reaction. The temperature in the chemical vapor deposition chamber is 600° C., and the pressure in the chemical vapor deposition chamber is 0.3 MPa. The introduction is stopped after 1.5 hours to obtain a dispersed silicon-carbon composite material.
[0037] Example 2
[0038] The rest is the same as Example 1, except that the amount of the dialdehyde mixture in step 3) is 480 g.
[0039] Example 3
[0040] The rest is the same as Example 1, except that the amount of the dialdehyde mixture used in step 3) is 180 g.
[0041] Example 4
[0042] The rest is the same as Example 1, except that the amount of the dialdehyde mixture in step 3) is 540 g.
[0043] Example 5
[0044] The rest is the same as Example 1, except that, in step 3), the dialdehyde mixture is prepared by mixing dodecanedial and 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde in a mass ratio of 5:7.
[0045] Example 6
[0046] The rest is the same as Example 1, except that in step 2), an equal mass of 2,2'-bithiophene-5,5'-dicarboxaldehyde is used to replace 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde.
[0047] Example 7
[0048] The rest is the same as Example 1, except that in step 2), an equal mass of triethylenetetramine is used to replace tetraethylenepentamine.
[0049] Example 8
[0050] The rest is the same as Example 1, except that the amount of tetraethylenepentamine used in step 2) is 400 g.
[0051] Example 9
[0052] The rest is the same as Example 1, except that the amount of urea used in step 4) is 2000 g.
[0053] Example 10
[0054] The rest is the same as Example 1, except that:
[0055] 2) 2000 g of alkali lignin and 600 g of tetraethylenepentamine were added to 8000 mL of water, the pH was adjusted to 11 with a 1 mol / L sodium hydroxide solution, and the mixture was stirred until completely dissolved. Under stirring conditions, 800 g of a 37 wt % formaldehyde solution was added to carry out a hydrothermal reaction at 80° C. for 1.5 h. After the reaction, isopropanol was added until no precipitation was produced, the mixture was filtered, washed with water until neutral, and dried at 80° C. until constant weight to obtain aminated alkali lignin;
[0056] 3) The aminated alkali lignin obtained in step 2) was dissolved in 8000 mL of a mixed solvent of dioxane and dichloromethane in a volume ratio of 7:3, 480 g of a dialdehyde derivative prepared by mixing dodecanedial and 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde in a mass ratio of 5:10 was added, and the mixture was heated to reflux for a cross-linking reaction for 4 h. After the reaction was completed, the mixture was filtered, washed with water 3 times, dried, and ground into 80 mesh to obtain a precursor;
[0057] 4) Take 1000g of the precursor prepared according to method 3) and mix it evenly with 2000g of urea, then heat it to 500℃ at a rate of 10℃ / min under a nitrogen atmosphere, and keep it at a constant temperature for 1h for carbonization. The carbonized material after carbonization is mixed evenly with a 30wt% sodium hydroxide solution at a mass volume ratio of 1g:4mL, and activate it in a nitrogen atmosphere. The activation procedure is to heat it to 800℃ at a rate of 10℃ / min and keep it at a constant temperature for 3h, cool it naturally to room temperature, wash it with a hydrochloric acid solution with a concentration of 1mol / L 3 times, wash it with water until it is neutral, and dry it at 60℃ to constant weight to obtain a porous carbon material with a semi-slope platform pore structure.
[0058] 5) After the chemical vapor deposition equipment is evacuated, the porous carbon material with a half-slope platform-type pore structure is placed in a chemical vapor deposition chamber, and a mixed gas consisting of argon and monosilane in a mass ratio of 10:90 is introduced at a flow rate of 120 mL / min for reaction. The temperature in the chemical vapor deposition chamber is 600° C., and the pressure in the chemical vapor deposition chamber is 0.2 MPa. The introduction is stopped after 1.5 hours to obtain a dispersed silicon-carbon composite material.
[0059] Comparative Example 1
[0060] The rest is the same as Example 1, except that, in step 3), all the dialdehyde derivatives are dodecanedial.
[0061] Comparative Example 2
[0062] The rest is the same as Example 1, except that, in step 3), all the dialdehyde derivatives are 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde.
[0063] Comparative Example 3
[0064] The rest is the same as Example 1, except that in step 2), an equal mass of 1,11-diaminoundecane is used to replace tetraethylenepentamine.
[0065] Application Example 1
[0066] Prepare the negative electrode of the battery:
[0067] Example 1 The dispersed silicon-carbon composite material, the conductive agent super P and the CMC binder are composed in a mass ratio of 8:1:1. The dispersed silicon-carbon composite material, the conductive agent super P and the CMC binder are uniformly dispersed in a solvent, coated on a 10 μm copper foil, dried at room temperature for 4 hours, and punched into a pole piece with a punch of 14 mm in diameter. -2 The tablets were pressed under pressure and placed in a vacuum oven at 120°C and dried for 8 hours.
[0068] Assemble the button cell battery:
[0069] In an argon-protected glove box, based on the above-mentioned battery negative electrode, the lithium sheet was used as the counter electrode, 1 mol / L LiPF6 solution (the volume ratio of EC, DMC, and EMC was 1:1:1) was used as the electrolyte, the celgard 2400 membrane was used as the diaphragm, and the button battery was assembled in a CR2016 battery shell.
[0070] Application Example 2-9
[0071] The rest is the same as Application Example 1, except that the dispersed silicon-carbon composite material is prepared according to Example 2-9.
[0072] Comparative Application Examples 1-3
[0073] The rest is the same as Application Example 1, except that the dispersed silicon-carbon composite material is prepared according to Comparative Examples 1-3.
[0074] The porous carbon materials prepared in the above examples and comparative examples were subjected to pore structure performance tests; the button batteries prepared in the application examples and comparative application examples were subjected to electrochemical performance tests:
[0075] Pore structure and specific surface area: measured by NOVA 1000e pore structure specific surface area tester. The sample was degassed at 350℃ for 2h, and liquid nitrogen was used as the adsorption medium at 77K and relative pressure (P / P0) 10 -6 N2 adsorption was carried out in the range of -1, and the specific surface area was calculated by BET equation.
[0076] Electrochemical performance: Constant current charge and discharge test of button cells was carried out on Wuhan Jinnuo LandCT2001A battery test system, and cycle charge and discharge were performed at 0.2C rate. The charge and discharge cut-off voltage was relative to Li / Li+ It is 0.005-2V.
[0077] Table 1 Test results
[0078]
[0079] Figure 1 This is the pore size distribution diagram of the porous carbon material prepared in Example 1 of the present invention. It can be seen that the pore size of the porous carbon material prepared in the present invention is mostly distributed in the range of about 1-10 nm, including a hierarchical structure in which small and concentrated micropores and small mesopores with a half-slope and wide-peak distribution coexist. It can be seen from the electrochemical performance test results that the dispersed silicon-carbon composite material prepared from the carbon material with such a pore structure is suitable for the preparation of silicon-carbon negative electrode materials for lithium-ion batteries, so that the electrode structure has good stability and the battery has excellent cycle stability.
[0080] Figure 2 The pore size distribution diagram of the porous carbon material prepared in Comparative Example 3 shows that the pore size is mainly concentrated in the range of 1-2nm, and its microporous structure is well developed, which is a typical microporous material, indicating that the number of residual amino groups of the polyamine grafted on the alkali lignin plays an important role in the evolution of the porous carbon material from a single structure dominated by micropores to a hierarchical porous structure with coexistence of micro / mesopores. From the performance test results of Application Example 1, Application Example 9, and Comparative Application Example 3 in Table 2, it can be seen that the amount of residual amino groups on the polyamine, combined with the porogen, makes the porous carbon material evolve from a single structure dominated by micropores to a hierarchical porous structure with coexistence of micro / mesopores, and gives the porous carbon material small and broad-peaked mesopores, that is, there is a half-slope platform-type mesoporous transition zone between the micropores and the macropores. This pore structure has good connectivity, and the silicon source gas can smoothly diffuse into the deep micropores inside the material, making full use of all adsorption sites, improving the dispersion uniformity of silicon particles in the porous carbon material, effectively reducing the generation of local defects, maintaining the stability of the electrode structure, and improving the cycle stability of the battery.
[0081] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous carbon material with a half-slope platform pore structure, characterized in that: The steps include: 1) adding alkali lignin and polyamine to water, adjusting the pH, stirring until completely dissolved, adding formaldehyde solution under stirring conditions for hydrothermal reaction, adding isopropanol after the reaction until no precipitation is produced, filtering, washing, and drying to obtain amination alkali lignin; 2) dissolving the amination alkali lignin in an organic solvent, adding a dialdehyde mixture, heating to reflux state to carry out a cross-linking reaction, filtering after the reaction, washing, drying, and grinding to obtain a precursor; 3) The precursor and the porogen are mixed evenly, and then carbonized under an inert atmosphere. The carbonized material is then mixed with an alkali solution and activated in an inert atmosphere, and then cooled, acid-washed, washed with water, and dried to obtain a porous carbon material with a semi-slope platform-type pore structure; Step 1) The polyamine is selected from one or a combination of two or more of diethylenetriamine, triethylenetetramine and tetraethylenepentamine, preferably tetraethylenepentamine.
2. The method for preparing the porous carbon material with a half-slope platform-type pore structure according to claim 1, characterized in that: Step 2) The dialdehyde mixture is a mixture of aliphatic dialdehyde and dialdehyde-based thiophene derivative in a mass ratio of 5:7-10.
3. The method for preparing the porous carbon material with a half-slope platform-type pore structure according to claim 2, characterized in that: Step 2) The aliphatic dialdehyde is a C8-C12 aliphatic dialdehyde, selected from one or a combination of two or more of heptanedialdehyde, octanedial, nonanedialdehyde, and dodecanedial, preferably dodecanedial; the aldehyde thiophene derivative is selected from one or a combination of two or more of 3,4-thiophene dicarboxaldehyde, 2,3-thiophene dicarboxaldehyde, 2,2'-bithiophene-5,5'-dicarboxaldehyde, 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde, preferably 2,2':5',2"-terthiophene-5,5"-dicarboxaldehyde.
4. The method for preparing the porous carbon material with a half-slope platform-type pore structure according to claim 1, characterized in that: Step 1) The mass ratio of the alkaline lignin, polyamine and formaldehyde solution is 15-20:4-6:5-8. The pH is adjusted to 10-11 with an alkali solution with a concentration of 0.5-1 mol / L; the hydrothermal reaction temperature is 40-80°C, and the reaction time is 1-3h; and the washing is washing with water until neutral.
5. The method for preparing the porous carbon material with a half-slope platform-type pore structure according to claim 1, characterized in that: The mass ratio of the dialdehyde mixture in step 2) to the polyamine in step 1) is 0.5-0.8:1; the reaction time is 4-6h; the organic solvent is selected from one or a combination of two or more of chloroform, pyridine, dichloromethane, ethanol, acetone, dioxane, and ethyl acetate, preferably a mixed solvent of dioxane and dichloromethane in a volume ratio of 7:2-4, preferably 7:
3.
6. The method for preparing the porous carbon material with a half-slope platform-type pore structure according to claim 1, characterized in that: Step 3) The mass ratio of the precursor to the porogen is 1:1-2; the porogen is selected from one or a combination of two or more of ammonium carbonate, urea, ammonium bicarbonate, ammonium formate, ammonium acetate, and ammonium oxalate.
7. A porous carbon material with a half-slope platform pore structure prepared by the method for preparing a porous carbon material with a half-slope platform pore structure according to any one of claims 1 to 6.
8. A method for preparing a dispersed silicon-carbon composite material, characterized in that: After evacuating a chemical vapor deposition device, the porous carbon material with a half-slope platform-type pore structure as described in any one of claims 1 to 6 or 7 is placed in a chemical vapor deposition chamber, and silicon source gas is introduced to perform vapor deposition of silicon to obtain a dispersed silicon-carbon composite material.
9. The method for preparing the dispersed silicon-carbon composite material according to claim 8, characterized in that: The temperature in the chemical vapor deposition chamber is 500-600°C; the time for introducing the mixed gas is 1-4h, the flow rate of the mixed gas is 120-180mL / min, the pressure in the chemical vapor deposition chamber is 0.1-0.3MPa, and the silicon source gas and the inert gas are mixed in a volume ratio of 5-10:90-95; the silicon source gas is selected from one or a combination of two or more of monosilane and disilane.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode, and the negative electrode comprises the dispersed silicon-carbon composite material according to claim 8 or 9.
Citation Information
Patent Citations
Nitrogen and sulfur doped hierarchical-pore carbon material, and preparation method and application thereof
CN110217792A
Preparation method of crosslinked polyamino acid-based porous carbon material
CN110272034A
Method for preparing high-specific-surface-area activated carbon with alkali lignin as raw material
CN110894071A
Plant cellulose modified adsorption material and preparation process thereof
CN112897629A
Lignin-based porous carbon material, preparation method and application thereof, and lithium ion energy storage device
CN116119661A